Physical and Chemical Properties of Bio-Compost Mixed with Cassava Leaves and Stems - Salitxay, Timnoy; KOUMBASITH, Somchan; CHASENGSONG, Kisong; PHOMLASABOUD, Khantavanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aimed to investigate the physical and chemical properties of bio-compost mixed with cassava leaves and stems at different mixing ratios. The experiment was conducted using a Completely Randomized Design (CRD) consisting of four treatments with three replications. The composting materials included cassava leaves and stems, rice husk, rice bran, and cow manure. The treatment compositions were as follows: T1= (33.3: 33.3: 33.3: 25), T2= (50: 25: 25: 25), T3 = (60: 20: 20: 25), and T4 = (66: 17: 17: 25). The compost was prepared according to the Nam Theun 2 Dam Project protocol. Cassava leaves and stems were ground and mixed with compost at different ratios of ground cassava leave and stem. After 30 days of composting, samples were collected and analyzed for physical properties (moisture content) and chemical properties including pH, electrical conductivity (EC), total nitrogen (N), phosphorus (P₂O₅), potassium (K₂O), carbon-to-nitrogen ratio (C/N), and organic matter (OM). Data were analyzed using Minitab 16.0 with a 95% significance level (p ≤ 0.05). The results showed significant differences among treatments (p≤ 0.05), except for pH, which showed no significant difference. Moisture content ranged from 65.54% to 71.85%. The highest EC value was observed in T4 (918.37 µS/cm), while T1 recorded the lowest (537.27 µS/cm). Total nitrogen content was highest in T3 (9.42%), followed by T4 (8.90%) and T2(8.74%). Phosphorus (P₂O₅) content was highest in T1 (0.56%) and lowest in T4 (0.34%). The highest potassium (K₂O) level was found in T2 (2.25%), while the lowest C/N ratio was observed in T4 (0.94%). Organic matter content was highest in T2 (21.34%). The germination index (GI) of treatment T2 was 115.3%, which is higher than the compost quality standard of 80%. This result indicates that the compost was mature and free of phytotoxic effects. Therefore, finding suggests that mixing cassava leaves and stems at appropriate ratio can enhance nutrient content and improve the overall quality of organic bio compost.